POTASSIUM 2-OXOIMIDAZOLIDINE-1,3-DIIDE AS A NOVEL CATALYST FOR GRIND SYNTHESIS OF PYRANO[4,3-b]CHROMENONE - Mohammad Nikpassand; Leila Zare Fekri; Zahra Gharib; Zeinab Jafarian (Journal of the Chilean Chemical Society, 2019)
A novel, clean, mild and eco-friendly benign route to pyrano[4,3-b]chromenes through cyclocondensation reaction of β-naphthol, aldehydes and 4-hydroxycoumarin, using POImD as a novel and reusable organometallic catalyst, is described. The present methodology offers several advantages such as simple work-up procedure, short reaction time, high yields of product with better purity and green aspect by avoiding toxic catalyst and hazardous solvent. All of synthesized compounds were characterized by IR, NMR and elemental analyses.